Relationships between Organizational Climate and Happiness at Work among Professional Nursesin SrisangwornSukhothai Hospital - Oumkaew, Kitjar; Daengthern, Laddawan (NU Journal of Nursing and Health Sciences, 2019)
The purposes of this descriptive research wereto study: 1) organizational climate as perceived by professional nurses in SrisangwornSukhothai Hospital 2) happiness at work among professional nurses as perceived by professional in SrisangwornSukhothai Hospital 3) the relationship between organizational climate and happiness at work among professional nurses as perceived by professional nurses in SrisangwornSukhothaiHospital.The samples comprised 140 professional nurses who had worked for more than one year at SrisangwornSukhothaiHospital selected by simple random sampling. The research tools comprised three sets of questionnaires asking about personnel data, organizational climate as perceived by professional nurses in SrisangwornSukhothaiHospital and happiness at work among professional nurses as perceived by the professional nurses in SrisangwornSukhothai Hospital. The reliability of the second and third parts of the questionnaire estimated by Cronbach'salphacoefficientswere0.97 and 0.89, respectively. The data were analyzed by frequency, percentage, average, standard deviation and Pearson' product correlation coefficient.The results showed that. 1) organizational climate as perceived by professional nurses in SrisangwornSukhothaiHospital overall, was at high level ( = 3.60, S.D.= 0.45) 2) happiness at work among professional nurses as perceived by using descriptive statistics for professional nurses in SrisangwornSukhothaiHospital was at high level ( = 3.49, S.D. = 0.50) 3) there was a statistical significantpositive correlation at the moderate level between organizational climate and happiness at work among professional nurses as perceived by professional nurses in SrisangwornSukhothaiHospital (r = 0.508, p < 0.01)